2022
DOI: 10.1039/d2tc02689a
|View full text |Cite
|
Sign up to set email alerts
|

High-performance semitransparent organic solar cells enabled by pseudo-planar heterojunction structures combined with optical engineering

Abstract: Semitransparent organic solar cells (ST-OSCs) are emerging as a promising renewable energy technology for building integration. However, how to solve the trade-off between power-conversion efficiency (PCE) and average visible transmittance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Transparent organic solar cells (T-OSCs), in particular, have advantages such as lightweight, transparency, solution processability, and mechanical flexibility, and they can be applied to building-integrated photovoltaics (BIPVs) or smart window technologies. To evaluate the performance of T-OSCs applied to windows, various parameters, such as the average photopic transmittance (APT), power conversion efficiency (PCE), and color rendering index (CRI), are utilized. ,, In particular, the APT, which is the brightness of an object as perceived by the human eye, is crucial because a higher APT can reduce electricity consumption while maintaining interior brightness and improve the quality of human life by providing an external view . However, since the APT and PCE have a trade-off relationship, research is required to increase the APT while maintaining a certain level of PCE. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transparent organic solar cells (T-OSCs), in particular, have advantages such as lightweight, transparency, solution processability, and mechanical flexibility, and they can be applied to building-integrated photovoltaics (BIPVs) or smart window technologies. To evaluate the performance of T-OSCs applied to windows, various parameters, such as the average photopic transmittance (APT), power conversion efficiency (PCE), and color rendering index (CRI), are utilized. ,, In particular, the APT, which is the brightness of an object as perceived by the human eye, is crucial because a higher APT can reduce electricity consumption while maintaining interior brightness and improve the quality of human life by providing an external view . However, since the APT and PCE have a trade-off relationship, research is required to increase the APT while maintaining a certain level of PCE. , …”
Section: Introductionmentioning
confidence: 99%
“…6 However, since the APT and PCE have a trade-off relationship, research is required to increase the APT while maintaining a certain level of PCE. 7,8 The formation of transparent top electrodes with a high APT and a low sheet resistance on photoactive layers has been considered the most challenging technical barrier in developing T-OSCs with both a high APT and a high PCE. 9−11 To overcome this barrier and fabricate efficient T-OSCs, pioneering researchers have explored various transparent top electrodes, including conducting polymers, silver nanowires, graphene, transparent conducting metal oxides, carbon nanotubes, and hybrids thereof.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 the device structure engineering enhances the PCEs without compromising their AVT, such as conducting polymer interlayer 25 and electrode modification with antireflection coating. 26,27 Herein, we demonstrate a strategy, using vertically stacked multiheterojunctions, to realize highly transparent and efficient ST-OPVs. 28,29 These vertical multiheterojunctions introduce cascading alignments of the lowest unoccupied molecular orbitals (LUMOs) and highest occupied molecular orbitals (HOMOs) to facilitate efficient charge extraction and transport in parallel to the device structure direction.…”
Section: Introductionmentioning
confidence: 99%
“…As an unfortunate consequence, ST-OPVs are often plagued by a trade-off between their PCEs and their average visible transmittances (AVTs). , Previously, we demonstrated that ST-OPVs incorporating sequentially deposited pseudo p – i – n active layers can successfully circumvent this trade-off between the AVT and PCE, with substantially improved performance over those of traditional ST-OPVs featuring BHJ active layers . Moreover, the device structure engineering enhances the PCEs without compromising their AVT, such as conducting polymer interlayer and electrode modification with antireflection coating. , …”
Section: Introductionmentioning
confidence: 99%
“…Promotion of BHJ ST-OPVs has fallen into bottleneck.Recently, pseudoplanar heterojunction (PPHJ) structure shows great potential application in ST-OPVs. [22][23][24][25] Donor and acceptor have gradient distribution in PPHJ structure. It was proved that PPHJ structure ensures efficient dissociation and diffusion of excitons as well as charge transporting.…”
mentioning
confidence: 99%